APPLICATION OF ARCH/GARCH MODELS IN ANALYSIS OF PRICE VOLATILITIES LOCAL, IMPORTS (USA), AND WORLD - Azkiya Naura Zahira; Ahmad Zainuddin (J-PEN Borneo : Jurnal Ilmu Pertanian, 2023)
Soybeans are one of Indonesia’s strategis agricultural commodities. Soybean prices fluctuation due to high demand and low stock of soybeans. This study was conducted to determine the behavior of local soybean prices in Indonesia, imported soybeans from the USA, and world soybeans. This study uses monthly soybean price time series data from January 2017 to March 2022 for local and world soybean price data and for imported soybean price data (USA) from January 2018 to March 2022. The data is obtained from the Kementrian Perdagangan, UN Comtrade, and the World Bank. The research method used is the ARCH/GARCH analysis method. The result of this study is the estimation of the GARCH model on the volatility of local soybean prices in Indonesia, imported soybeans (USA), and world soybeans obtained the GARCH (1,1) model. Based on the GARCH (1,1) model, the price of local soybeans in Indonesia is more volatile than the price of imported soybeans (USA) and the price of world soybeans is more volatile than the price of imported soybeans (USA). The prices of local soybeans in Indonesia, imported soybeans, and world soybeans are more volatile after the Covid-19 pandemic than before the Covid-19 pandemic. Future forecasts of local soybean prices in Indonesia, imported soybeans, and world soybeans are predicted to increase with the highest price in December 2024 of IDR 15,391.21 for local soybeans, IDR 11,303.92 for imported soybeans, and IDR 12,069.11 for world soybeans. This price forecast can be used as a reference by the government in planning soybean import policies.